Beyond the Biophysical Knowledge, Culture, and Power in Agriculture and Natural Resource Management - German, Laura; Ramisch, Joshua J.; Verma, Ritu (Springer Netherlands : Imprint: Springer, 2010)
Beyond the Biophysical argues for an interdisciplinary perspective on agriculture, natural resource management (NRM), and international development practice that extends beyond a purely biophysical orientation. Biophysical interventions succeed or fail not simply on their own merits but within a context shaped by knowledge, culture, and power. The original case studies and conceptual syntheses (from Africa, Asia, and Latin America) analyze some of the challenges and "misadventures" associated with past and current development approaches and practice. They apply contemporary, critical social science to make sense of these realities and offer concrete recommendations for moving beyond them. With them, we hope to make social science theory, the challenges faced by socio-cultural scientists working in arenas dominated by other disciplines, and the potentially unique contributions of social science to agriculture and natural resource management more accessible to biophysical scientists, development practitioners, and those exploring the socio-cultural sciences as a possible career path. The book is broken into four main sections: (1) an introduction to concepts and the volume; (2) a series of chapters designed to foster a rethinking of common concepts and assumptions in agricultural development and natural resource management; (3) a set of case studies and conceptual overviews on the interface of knowledge, culture, and politics; and (4) a set of chapters on institutional disconnects and innovations to expand institutionalized thinking and practice.